2012
DOI: 10.1118/1.4770286
|View full text |Cite
|
Sign up to set email alerts
|

Projection imaging of photon beams by the Čerenkov effect

Abstract: Purpose: A novel technique for beam profiling of megavoltage photon beams was investigated for the first time by capturing images of the inducedČerenkov emission in water, as a potential surrogate for the imparted dose in irradiated media. Methods: A high-sensitivity, intensified CCD camera (ICCD) was configured to acquire 2D projection images ofČerenkov emission from a 4 × 4 cm 2 6 MV linear accelerator (LINAC) x-ray photon beam operating at a dose rate of 400 MU/min incident on a water tank with transparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
137
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(142 citation statements)
references
References 53 publications
2
137
0
Order By: Relevance
“…Many of these dosimeters make use of the concept of tomography to reconstruct a 3D scintillation volume from many different perspectives (or projections). [15][16][17] While these techniques have shown potential to perform accurate dosimetry on a whole 3D volume, their application to dynamic, modulated radiation delivery is not straightforward, since components of the dosimeter need to rotate during acquisition, a fact which limits their real-time capability. Some other approaches use only fixed components to image and reconstruct a scintillating volume in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these dosimeters make use of the concept of tomography to reconstruct a 3D scintillation volume from many different perspectives (or projections). [15][16][17] While these techniques have shown potential to perform accurate dosimetry on a whole 3D volume, their application to dynamic, modulated radiation delivery is not straightforward, since components of the dosimeter need to rotate during acquisition, a fact which limits their real-time capability. Some other approaches use only fixed components to image and reconstruct a scintillating volume in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…In air, given the low index of refraction, electrons must have energy greater than 20.3 MeV to produce Cherenkov radiation, which is beyond the range of most medical linear accelerators (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Several studies have however utilized Cherenkov radiation generated in water and tissue for dosimetry [22][23][24][25] and molecular imaging. [26][27][28][29][30] While much weaker than Cherenkov radiation, air scintillation can probe and monitor the characteristics of a beam before it enters a patient, in a minimally perturbing manner (perturbation of the beam by air always occurs, independent of our measurement).…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] It has been shown that, above the threshold energy forČerenkov radiation (approximately 220 KeV in biological tissue), under the approximation of charged particle equilibrium, the dose deposited by megavoltage radiotherapy radiation, and the number ofČerenkov photons released locally are directly proportional; therefore, beam profiling and superficial dosimetry imaging based onČerenkov radiation is feasible. [34][35][36] Radiation dose is calculated by D = E max 0…”
Section: Introductionmentioning
confidence: 99%